Konstruksi Realitas Sosial melalui Algoritma Media Digital dalam Perspektif Ilmu Sosial Modern Indonesia - Fathilah, Sultan Akrabu; Fitrayani, Ana; Bahtiar, Syamsul (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2025)
This study examines the construction of social reality through digital media algorithms from the perspective of modern Indonesian social sciences. The primary focus lies on algorithms as non-neutral mechanisms that actively shape information flows, interaction patterns, and the production of social meaning in the digital public sphere. Algorithms operate through processes of selection, personalization, and content prioritization, which directly influence how individuals perceive social reality, form opinions, and construct identities and social affiliations. The study is grounded in social construction of reality theory, contextualized within the development of digital media and algorithmic logic. The research adopts a qualitative approach with a critical analytical design to examine algorithmic practices in Indonesian digital media. Data were collected through document analysis, digital media discourse analysis, and a systematic review of relevant empirical studies. The analysis employed a thematic strategy to identify relational patterns between algorithms, discursive production, and user responses. The findings demonstrate that digital media algorithms function as structural actors that reinforce filter bubbles, echo chambers, and the commodification of social discourse. In the Indonesian context, algorithmic constructions of social reality intersect with cultural, religious, and political dynamics, producing curated forms of reality that carry a high potential for social polarization. This study underscores the urgency of algorithmic literacy, platform transparency, and public policy interventions to safeguard the quality of the digital public sphere. Academically, the research contributes to the advancement of interdisciplinary approaches within social sciences and humanities in the digital era.